Portraying Informal Digital Learning of English from Management, Beliefs, and Practices - Surya Agung Wijaya; Abdul Asib; Suparno Suparno (UIN Salatiga, 2021)
In a couple of years, massively multiplayer online role-playing game (MMORPG) previous works reported various informal digital learning of English (IDLE) activities within and around video games that could enhance student-gamer vocabulary outcomes; receptive and productive language skills; and language socialization. The lack of multidisciplinary literature reviews between IDLE and language policy (LP) gives this study to open discussion on both areas. The urgency of this study is the high adoption of IDLE framework without considering LP where the reason for student’s engagement from MMORPG activities can be explained. This study aims to portray IDLE practitioner's activities in MMORPG from language management, beliefs, and practices. Following the long-term process, the data were generated from auto-ethnography and photo-elicitation that were taken from in-game and out-of-game activities. This article found three major findings. First, the management of MMORPG provoked gamers to communicate as a part of the game mission, and the guild could potentially develop top-down and bottom-up LP. Second, the value of language in the community played role in the decision-making language use from the negotiation process. Third, English and Mandarin dominated language practices from different interlocutors in various forms such as language in MMORPG’s context, code mixing, and abbreviation from multilingual sides giving various reading texts in contexts. The high status of English is still dominated by out-of-game language practices. There are two major implications in theory and praxis that would be discussed in this study.Keywords: Auto-ethnography, IDLE, language policy, MMORPG, and multilingual environment